2008
DOI: 10.1124/mol.107.043034
|View full text |Cite
|
Sign up to set email alerts
|

Niemann-Pick C1-Like 1 Mediates α-Tocopherol Transport

Abstract: Dietary lipids and fat-soluble micronutrients are solubilized in mixed micelles and absorbed in the small intestine. Based on an assumption that cholesterol and other fat-soluble molecules share a number of transport mechanisms and the fact that Niemann-Pick C1-like 1 (NPC1L1) is critical for intestinal cholesterol absorption, we hypothesized that some fat-soluble molecules may be transported by NPC1L1. To investigate this hypothesis, we compared the cellular uptake and inhibitory effects of ezetimibe, the mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
109
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(120 citation statements)
references
References 27 publications
8
109
0
3
Order By: Relevance
“…Elle est incorporee dans les micelles mixtes issues de la digestion des lipides et est absorbee dans le duodenum. Les transporteurs scavenger receptor type B1 (SR-B1) (Reboul et al, 2006) et Niemann-Pick C1-like 1 (NPC1L1) (Narushima et al, 2008) sont impliques dans cette absorption. Il est admis que la vitamine E est incorporee sous forme libre dans les chylomicrons.…”
Section: Absorption Et Metabolisation De La Vitamine Eunclassified
“…Elle est incorporee dans les micelles mixtes issues de la digestion des lipides et est absorbee dans le duodenum. Les transporteurs scavenger receptor type B1 (SR-B1) (Reboul et al, 2006) et Niemann-Pick C1-like 1 (NPC1L1) (Narushima et al, 2008) sont impliques dans cette absorption. Il est admis que la vitamine E est incorporee sous forme libre dans les chylomicrons.…”
Section: Absorption Et Metabolisation De La Vitamine Eunclassified
“…These results suggest that CoQ10 may be a substrate of NPC1L1 as is the case for vitamin E. Although NPC1L1 is known to be a sterol transporter in the intestine, NPC1L1-overexpression appears to facilitate the accumulation of α-tocopherol, which does not have a sterol structure, in an ezetimibe-sensitive manner. 5,14) Abuasal et al reported that the intestinal absorption of γ-tocotrienol is partly mediated by NPC1L1. 23) We also reported that NPC1L1 is partly involved in the absorption of lutein, a dihydroxycarotenoid.…”
Section: Effect Of Cholesterol In Lipid Emulsion Particles On the Uptmentioning
confidence: 99%
“…However, not only cholesterol but also other lipophilic molecules such as vitamin E and lutein have been recently reported to be solubilized in lipid emulsion particles and then partly absorbed in the intestine via NPC1L1. 5,6) NPC1L1 has been predicted to incorporate cholesterol and other parts of lipophilic molecules from mixed micelles into enterocytes via clathrin-mediated endocytosis. 7,8) As just described, the intestinal uptake mechanism of substrates of NPC1L1 has been gradually demonstrated.…”
mentioning
confidence: 99%
“…The intestinal cellular uptake of vitamin E from mixed micelles follows in principle two different pathways across enterocytes, as has been shown in vitro and in vivo: (1) passive diffusion; and (2) receptor-mediated transport. Receptors facilitating α-TOH transport across the enterocyte membrane, similar to the intestinal uptake of cholesterol [54] , are the class B type 1 scavenger receptor class B type 1 (SR-B1) [55] and the Niemann-Pick C1-like protein 1 (NPC1L1), an apical membrane receptor of the small intestine [56] . The ATP-binding cassette (ABC) transporters ABCG5/ABCG8, at the luminal site, and ABCA1, at the apical site, are responsible for steroid efflux into the intestinal lumen and transport into the lymph system, respectively [57,58] .…”
Section: Intestinal Absorptionmentioning
confidence: 99%